If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x-(2x+15)=7-(5x-5)
We move all terms to the left:
4x-(2x+15)-(7-(5x-5))=0
We get rid of parentheses
4x-2x-(7-(5x-5))-15=0
We calculate terms in parentheses: -(7-(5x-5)), so:We add all the numbers together, and all the variables
7-(5x-5)
determiningTheFunctionDomain -(5x-5)+7
We get rid of parentheses
-5x+5+7
We add all the numbers together, and all the variables
-5x+12
Back to the equation:
-(-5x+12)
2x-(-5x+12)-15=0
We get rid of parentheses
2x+5x-12-15=0
We add all the numbers together, and all the variables
7x-27=0
We move all terms containing x to the left, all other terms to the right
7x=27
x=27/7
x=3+6/7
| x-3-10=0 | | 18-0.16777(6g+18)=-2g-14 | | 7u+4=23 | | 18-1/6(6g+18)=-2g-14 | | 2/7n-2=4 | | 14-0.5(4p+12)=3p-15 | | 2w-5=12 | | 14-1/2(4p+12)=3p-15 | | (2x+5)^1/4=2 | | -5/3r=-35/12 | | 6y+12-6y=8 | | 2a÷3=4a÷5+7 | | 9p+5=12 | | 7^x+9=4 | | 3^5x=12 | | 5(2y-7)-4y=6(y-5)-3 | | 3(5x-1)-3(2x-10)=2(4x+2)-2 | | 3(5x-1)-3(2x-10)=2(4x+2)=2 | | 2z2+11z+15=0 | | 3x^2+27x-4.5=0 | | 3x-(5x+16)=3-(8x-4) | | (4–u)(2u+7)=0 | | 4+5r-2=8r+4-5r | | 4x+5/7=x+2/3 | | -5t^2+30t+30=0 | | 3x^2+27x+4.5=0 | | (4x)/(3)-x=(x)/(15)-(12)/(5) | | 3(m-10)+2(m-29)=2 | | 15-1/2(2s+10)=-2s-12 | | 15p+8=13+4p | | 10v-5=15 | | 6x8=40 |